2013
DOI: 10.1177/1071100712460215
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Botulinum Toxin A and Intralesional Steroids for the Treatment of Plantar Fasciitis

Abstract: Level I, therapeutic studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
57
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 31 publications
1
57
0
1
Order By: Relevance
“…(7) One study (18) reported better results in the botulinum toxin A injection group (intervention group) compared to the corticosteroid injection group. The remaining four studies (15,16,19,21) showed significant pain reduction in both intervention groups at follow-up intervals when compared to baseline but no significant differences between the intervention groups.…”
Section: Patient-assessed Outcome: Foot Painmentioning
confidence: 99%
See 4 more Smart Citations
“…(7) One study (18) reported better results in the botulinum toxin A injection group (intervention group) compared to the corticosteroid injection group. The remaining four studies (15,16,19,21) showed significant pain reduction in both intervention groups at follow-up intervals when compared to baseline but no significant differences between the intervention groups.…”
Section: Patient-assessed Outcome: Foot Painmentioning
confidence: 99%
“…The majority of studies investigated the use of palpation-guided corticosteroid injections, (7,15,16,(18)(19)(20)(21) while two studies (14,17) looked solely at US-guided corticosteroid injections. Only one study by Ball et al (13) included both palpation-and US-guided corticosteroid injections for comparison against a placebo; however, no significant differences in heel pain reduction between the US-and palpation-guided corticosteroid injection groups were found.…”
Section: Us-and Palpation-guided Corticosteroid Injectionsmentioning
confidence: 99%
See 3 more Smart Citations